Diffusion-Weighted Imaging of the Head and Neck in Healthy Subjects: Reproducibility of ADC Values in Different MRI Systems and Repeat Sessions - Kolff-Gart, A.S. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: DWI is typically performed with EPI sequences in single-center studies. The purpose of this study was to determine the reproducibility of ADC values in the head and neck region in healthy subjects. In addition, the reproducibility of ADC values in different tissues was assessed to identify the most suitable reference tissue. MATERIALS AND METHODS: We prospectively studied 7 healthy subjects, with EPI and TSE sequences, on 5 MR imaging systems at 3 time points in 2 institutions. ADC maps of EPI (with 2 b-values and 6 b-values) and TSE sequences were compared. Mean ADC values for different tissues (submandibular gland, sternocleidomastoid muscle, spinal cord, subdigastric lymph node, and tonsil) were used to evaluate intra- and intersubject, intersystem, and intersequence variability by using a linear mixed model. RESULTS: On 97% of images, a region of interest could be placed on the spinal cord, compared with 87% in the tonsil. ADC values derived from EPI-DWI with 2 b-values and calculated EPI-DWI with 2 b-values extracted from EPI-DWI with 6 b-values did not differ significantly. The standard error of ADC measurement was the smallest for the tonsil and spinal cord (standard error of measurement = 151.2 × 10(−6) mm/s(2) and 190.1 × 10(−6) mm/s(2), respectively). The intersystem difference for mean ADC values and the influence of the MR imaging system on ADC values among the subjects were statistically significant (P < .001). The mean difference among examinations was negligible (ie, <10 × 10(−6) mm/s(2)). CONCLUSIONS: In this study, the spinal cord was the most appropriate reference tissue and EPI-DWI with 6 b-values was the most reproducible sequence. ADC values were more precise if subjects were measured on the same MR imaging system and with the same sequence. ADC values differed significantly between MR imaging systems and sequences.